Acetabular fractures classification of Letournel and Judet--a systematic approach. - Saterbak, A. M. (University of Iowa, 1995)
After a background understanding of the classification of Judet and Letournel and the radiographic anatomy of the pelvis, the majority of acetabular fractures are readily classified by utilizing the steps as outlined above. We feel that a systematic, stepwise approach to classifying acetabular fractures into larger groups and then subclassifying these groups will help simplify the application of the Letournel and Judet classification. Try using this method, and your ability to classify these fractures will improve.